Obtención de bioetanol a partir de los azúcares reductores totales de la cáscara de plátano del mercado … - Martínez Vásquez, Mily Gissela (2015)
In the present investigation called "obtaining bioethanol from banana peel residue Ayaymama market - Moyobamba City 2014"has obtained a 3.4% bioethanol from green rind; and 3.0% for Shell mature, taking as a substrate of the alcoholic fermentation of the sugars reducers totals of the residue of banana peel, extracted by the physical method of autoclaving and determined by Folin and Wu method, having obtained a concentration of 1.6 g/L for green rind and 1. 7 g/L for shell mature. For this was considered to be evaluation parameters during the process to average environmental temperature that was 25 oc +-/ 3°C, pH for the green rind was 3.4% to 5.8 and 3 per cent to 5.3 in mature shell; and the concentration of reducing sugars totals of bioethanol, having determined that the concentration of ART 1.6 g/L were obtained a higher percentage of bioethanol (3,4 %) and the concentration of 1,7 g/L was obtained a maximum percentage of bioethanol from 3,0 %. and the concentration of reducing sugars totals of bioethanol, having determined that the concentration of ART 1.6 g/L were obtained a higher percentage of bioethanol (3,4 %) and the concentration of 1, 7 g/L was obtained a maximum percentage of bioethanol from 3,0 % .. Having made the research hypothesis under the assumption that the level of concentration of reducing sugars totals determines the percentage of bioethanol obtained from banana peel, it is concluded that the increase in the concentration of art of husk green plantain and mature influences the production of bioethanol. In the methodological framework, the research was conducted under a design in a randomized complete block with five treatments for the various concentrations of reducing sugars totals and five blocks for the different times of fermentation in the bioreactors. During the process were considered five stages: preparation, removal of the reducing sugars totals, determination of the total reducing sugars, installation on the bioreactors and fermentation, with sorne modifications specified in the protocol developed. The samples that were obtained from the bioreactors were on the third day, sixth day, ninth day, 11th day and fifteenth day. These samples were analyzed in the laboratory to determine the percentages of bioethanol. Key words: banana peel residue; alcoholic fermentation.